Risk factors and prevention of atrial fibrillation in the postoperative period after coronary artery bypass grafting: a literature review - M. A. Kuzmichkina; V. S. Kaveshnikov (Сеченовский вестник, 2024)
The increasing volume of coronary artery bypass grafting inevitably contributes to a growing number of postoperative complications. Atrial fibrillation (AF) develops in every second or third patient. This complication prolongs inpatient stays and increases costs of the healthcare system. The review presents data on the risk factors for postoperative AF, as well as the proposed methods of prevention and treatment. The research results indicate the role of type 2 diabetes mellitus, obesity, arterial hypertension; among laboratory parameters, mean platelet volume, red blood cell distribution width, C-reactive protein, erythrocyte sedimentation rate, monocyte/high-density lipoprotein cholesterol ratio are of prognostic value. Drug and non-drug methods of prevention and treatment of postoperative AF are discussed. The methods indicated in the presented works showed effectiveness, but had a number of limitations.